Detection of bacteria in suspension by using a superconducting quantum interference device - Grossman, H. L. (National Academy of Sciences, 2004)
We demonstrate a technique for detecting magnetically labeled Listeria monocytogenes and for measuring the binding rate between antibody-linked magnetic particles and bacteria. This sensitive assay quantifies specific bacteria in a sample without the need to immobilize them or wash away unbound magnetic particles. In the measurement, we add 50-nm-diameter superparamagnetic magnetite particles, coated with antibodies, to an aqueous sample containing L. monocytogenes. We apply a pulsed magnetic field to align the magnetic dipole moments and use a high-transition temperature superconducting quantum interference device, an extremely sensitive detector of magnetic flux, to measure the magnetic relaxation signal when the field is turned off. Unbound particles randomize direction by Brownian rotation too quickly to be detected. In contrast, particles bound to L. monocytogenes are effectively immobilized and relax in about 1 s by rotation of the internal dipole moment. This Néel relaxation process is detected by the superconducting quantum interference device. The measurements indicate a detection limit of (5.6 ± 1.1) × 10(6) L. monocytogenes in our sample volume of 20 μl. If the sample volume were reduced to 1 nl, we estimate that the detection limit could be improved to 230 ± 40 L. monocytogenes cells. Time-resolved measurements yield the binding rate between the particles and bacteria.